Comparison of the degradability of various polyethylene films containing pro-oxidant additive - Trang, Pham Thu; Huy, Nguyen Quang; Khoi, Nguyen Van; Thu Ha, Pham Thi; Tung, Nguyen Thanh (Vietnam Journal of Chemistry, 2016)
This study aims to compare the effect of the type of polyethylene matrix (HDPE, LLDPE) and evaluate the role of pro-oxidant additive on the degradation of PE film samples. The degradability of HDPE, LLDPE films without and with pro-oxidant (0, 1 and 3% w/w) was studied. Thermo-oxidative degradation of PE films was carried out in an oven at 80 oC for a maximum period of 7 days. The progress of thermo-oxidative degradation was measured by monitoring physical and chemical changes of films such as mechanical properties, FTIR and SEM. The results showed that, whatever the pro-oxidant used, the HDPE matrix is less efficiently oxidized than LLDPE matrix. Tensile strength and elongation at break decreased during treatment. FTIR traces exhibited that carbonyl group’s peak in the region 1700-1800 cm-1 arises during thermal treatment as a result of oxidation. The degradation rate of PE films increased by increasing the amount of pro-oxidant additive incorporated.